Ethnobotany of sugar palm (Arenga pinnata) in the Sasak Community, Kekait Village, West Nusa Tenggara, Indonesia - anggit haryoso; Ervizal Amzu; Agus Hikmat; Arzyana Sunkar; Dudung Darusman (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Haryoso A, Zuhud EAM, Hikmat A, Sunkar A, Darusman D. 2020. Ethnobotany of sugar palm (Arenga pinnata) in the Sasak Community, Kekait Village, West Nusa Tenggara, Indonesia. Biodiversitas 21: 117-128. Sugar palm (Arenga pinnata Merr.) is one kind of palm that has high potential ecological, economic, and socio-cultural values. This Research aimed to identify the ethnobotanical aspects of sugar palm, especially on aspects related to farmers characteristics, cultivation, utilization, cooking process of palm sugar sap and sugar palm marketing at the Kekait Village, West Lombok District, West Nusa Tenggara Province. Data were collected using participatory observation, in-depth interviews, literature studies, and the selection of informants conducted by purposive sampling. Sugar palm farmers were adult men aged between 42 to 63 years old. They achieved life skills provision from parents to their children. The characteristics of sugar palm farmers in the Sasak community are adult men to the elderly, aged 24-63 years. The source of knowledge about the use of sugar palm is hereditary from parents (father or grandfather). Oil palm farmers in the Sasak community in Kekait Village do not carry out intensive cultivation systems, they still rely on natural services, both regeneration and distribution. The most widely used part of the palm tree is tassel (76.32%), to be tapped. Processing palm sugar into sugar is still carried out with traditional methods and tools, as well as natural ingredients. Sugar palm farmers in Kekait Village were very dependent on small collectors who sell their sugar products. Farmers are in the weakest position in the marketing chains and did not have a bargaining position to determine the price of palm sugar.